Frequency and Prognostic Value of ABO Blood Groups in Patients with Hypertension, Obesity, Diabetes Mellitus, and Anemia in Local Population of Al-Najaf City/ Iraq - Shaimaa Jaber K.; Huda A. Saleh; Rajaa A. Hussein (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study was designed to investigate the distribution of ABO blood types and the possible association of hypertension, diabetes mellitus, obesity, and anemia diseases with ABO types. A total of 535 individuals 277 (51.77% males and 258 (48.22% females) were participating in the present study. Among them, 389 healthy subjects (187 (48.07% males and 202 (51.92% females) as well as 146 patients 90 (61.60%) males and 56 (38.40% females), 67 (37.85 % had hypertension, 51 (28.81%) had DM, 29 (16.38% had obesity and 30 (16.94%) subjects had anemia, the participants were attending hospitals, clinics, and laboratories. The demographic and clinical details, including ABO blood groups, blood glucose, blood pressure, blood hemoglobin as well as height and weight were obtained for both groups. Data analysis was done using the Chi-square test for comparing data. Based on the results, O blood type was the most common group with a percentage of (43.18% and 47.26%) followed by A type (25.44% and 26.02%) then B (22.87% and 13.01%), and AB (8.48% and 13.69%) respectively for healthy and non-healthy individuals. Hypertension and diabetes mellitus diseases were the greatest percentage (37.85% and 28.81%) respectively comparing with obesity (16.38%) and anemia (16.94%). The present study indicated that individuals of blood group O and A (52.48% and 23.75%, respectively) were more susceptible to diseases as compared with patients of blood group B (12.70%) and AB (11.04%). Our results suggested that the relative risk for hypertensive and diabetic patients was found to be higher in blood group AB (45% and 35% respectively) and lower in blood group O (36.84% and 25.26% respectively); high incidence of obesity was found in type O blood (24.21%) compared to other ABO types, while anemia was prone for patients with A blood group (20.93%). The results showed no association between ABO blood groups with hypertension, diabetes mellitus, obesity, and anemia diseases.